2008
DOI: 10.1089/apc.2007.0166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Sexually Transmitted Infections among South Indians at Increased Risk of HIV Infection

Abstract: Sexually transmitted infections (STIs) have been identified as cofactors of HIV transmission. Greater understanding of local STI burdens can assist in the development of more effective STI and HIV prevention strategies. The aim of this study is to determine the prevalence and incidence of STIs among South Indian men and women identified to be at increased risk for HIV infection. Individuals at increased risk for HIV infection were enrolled in a prospective longitudinal study in Chennai, India (n ϭ 480) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…STD patients with high risk sex behaviour can be co-infected with HIV and other STDs like syphilis, vaginitis etc. 20 In this study too, proportionally more STDs were identified in HIV positive patients though not statistically significant. Again STDs are (Table 7) more in HIV positive versus (v/s) negative.…”
Section: Association With Other Stdsmentioning
confidence: 47%
“…STD patients with high risk sex behaviour can be co-infected with HIV and other STDs like syphilis, vaginitis etc. 20 In this study too, proportionally more STDs were identified in HIV positive patients though not statistically significant. Again STDs are (Table 7) more in HIV positive versus (v/s) negative.…”
Section: Association With Other Stdsmentioning
confidence: 47%
“…However, in the last few years, this infection has been placed among the most common in high-risk population groups in India (Kumarasamy et al, 2008). Data taken from FSW sample groups show that a high percentage of them are infected with HSV-2, reporting a prevalence of 56 to 73% (Shahmanesh et al, 2009;Uma et al, 2005;Wayal et al, 2011).…”
Section: Evidence Of Sti In Indiamentioning
confidence: 99%
“…Surveillance data indicates that about 170-190 million including 76.5 million new cases are reported annually in South East Asia (WHO, 2012). In India, trichomoniasis accounts for 1.2-28.5% amongst commercial sex workers, general community and migrated population and 61.7% in women attending STD clinics (WHO, 2005;Kumarasamy et al, 2008;Kaur et al, 2008;Sood et al, 2008;Shethwala et al, 2009;Shahmanesh, et al, 2009;Madhivanan et al, 2009;Preethi et al, 2011;Paul et al, 2012;Fule et al, 2012;Dave et al, 2012;Dharma et al, 2013;Desai et al, 2013;Arora et al, 2014). One of the reasons for this wide variation in prevalence could be use of diagnostic assays that are highly variable in sensitivity and specificity (Schwebke et al, 2004;Radonjic et al, 2005;Nye et al, 2009;Unemo et al, 2013;Sonkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%